On The Boundary Behavior of Regular Solutions of the Degenerate Beltrami Equations - Lomako, T.V. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study the boundary behavior of regular solutions to the degenerate Beltrami equations with constraints of the integral type imposed on the coefficient.